Energy consumption for ion-transport in a segmented Paul trap. (12th June 2018) - Tobalina, A; Alonso, J; Muga, J G
Abstract: There is recent interest in determining energy costs of shortcuts to adiabaticity (STA), but different definitions of 'cost' have been used. We demonstrate the importance of taking into account the control system (CS) for a fair assessment of energy flows and consumptions. We model the energy consumption and power to transport an ion by a STA protocol in a multisegmented Paul trap. The ion is driven by an externally controlled, moving harmonic oscillator. Even if no net ion-energy is gained at destination, setting the time-dependent control parameters is a macroscopic operation that costs energy and results in energy dissipation for the short time scales implied by the intrinsically fast STA processes. The potential minimum is displaced by modulating the voltages on control (dc) electrodes. A secondary effect of the modulation, usually ignored as it does not affect the ion dynamics, is the time-dependent energy shift of the potential minimum. The non trivial part of the energy consumption is due to the electromotive forces to set the electrode voltages through the low-pass filters required to preserve the electronic noise from decohering the ion's motion. The results for the macroscopic CS (the Paul trap) are compared to the microscopic power and energy of the ion alone. Similarities are found—and may be used quantitatively to minimize costs—only when the CS-dependent energy shift of the harmonic oscillator is included in the ion-energy.